KAJIAN TIPOLOGI KONFIGURASI SONASI DAN FURNITURE PADA INTERIOR COFFEE SHOP DI DENPASAR - Ardina Susanti (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2017)
Abstract:. Drinking coffee is a worldwide culture. Because the culture is now a global culture, then this culture was made commercially with the creation of a coffee shop. Coffee shop functions are growing, along with the development of lifestyle and social life of the surrounding community culture. With the evolving and changing function of the coffee shop, the interior configuration is definitely changed, especially in the configuration of space and furniture. Therefore, this study aims to examine the typology of the configuration of the sonasi and the interior furniture of the existing coffee shop, and to analyze the causal factors of the typology. Data collection method used is the method of observation, accompanied by qualitative data analysis method. The result of this research is furniture and sonasi configuration will arrange spatial organization that determine the tendency of function of a room / interior and function that runs in a coffee shop / coffee shop is very influenced by lifestyle that is developing Keyword: Coffee shop, furniture, interior, configuration, sonasi, typology Abstrak: Minum kopi merupakan suatu budaya yang mendunia. Oleh karena budaya tersebut kini menjadi budaya global, maka budaya ini pun dibuat komersial dengan diciptakannya coffee shop. Fungsi coffee shop pun semakin berkembang, seiring dengan perkembangan gaya hidup dan kehidupan sosial budaya masyarakat sekitarnya. Dengan berkembang dan berubahnya fungsi dari coffee shop, maka konfigurasi interiornya pun pasti berubah, terutama pada konfigurasi sonasi ruang dan furniture. Oleh karena itu, penelitian ini bertujuan untuk mengkaji tipologi konfigurasi sonasi dan furnitur interior coffee shop yang ada, dan menganalisa faktor – faktor penyebab dari adanya tipologi tersebut. Metode pengumpulan data yang digunakan adalah metode observasi, disertai dengan metode analisis data kualitatif. Hasil dari penelitian ini adalah konfigurasi furniture dan sonasi akan menyusun organisasi spasial yang menentukan kecenderungan fungsi suatu ruang/interior dan fungsi yang berjalan dalam suatu kedai kopi/coffee shop sangat dipengaruhi oleh gaya hidup yang sedang berkembang Kata Kunci: Coffee shop, furniture, interior, konfigurasi, sonasi, tipologi